CODE-SWITCHING AND CODE-MIXING IN EGYPTIAN ONLINE NEWS (ON THE BASIS OF YOUTUBE CHANNELS 'JOE SHOW ALARABY' AND 'MOKHBIR EQTISADI') (BULLETIN OF TARAS SHEVCHENKO NATIONAL UNIVERSITY OF KYIV. ORIENTAL LANGUAGES AND LITERATURES, 2025)
Introduction. In the global multilingual media space, YouTube blogs are increasingly replacing traditional news platforms, which activates language code-switching and mixing. The provided study aims to outline the sociolinguistic and linguopragmatic features of the content of Egyptian channels Mokhbir Eqtisadi and Joe Show Alaraby. The purpose of this study is to identify the types of code-switching and the factors influencing it’s use.Methods. A comprehensive methodology was applied: lexical-semantic analysis (identification of dialectisms and anglicisms), comparative analysis (comparison of the language practices of the two channels), sociolinguistic and linguopragmatic approaches (determination of the role of subject matter, genre and target audience), as well as elements of discourse analysis and other. Results. The dominance of the Egyptian dialect with numerous English insertions (brand names, digital terminology) and French everyday words was established. The following features of code-switching and code-mixing were recorded: intersential and intrasential switching between MSA and a dialect; tag switching (in particular, when addressing the audience) between Arabic and English; code-mixing through occasional use of English borrowings or colloquial words. In addition, code-mixing was found at the lexical and phonographic levels: the use of English names in Arabic script, the spelling of brands in Latin script, intralexical mixing, and the combination of text and numbers in writing. The content of Mokhbir Eqtisadi contains code-switching and code-mixing primarily for the purpose of informing and engaging a wider audience; in Joe Show Alaraby, different language codes and foreign lexemes function to provide a comic effect.Conclusions. The analysis of news video content revealed active code-switching and code-mixing between MSA, a dialect and, to a lesser extent, English. Various types of code-switching and code-mixing, as well as individual foreign language insertions, were used to achieve communicative goals of informing, interacting and expanding the audience, and creating a comic effect. The use of borrowings from the Internet slang demonstrated the English language’s prestige and the bloggers' desire to bring their speech closer to young people. On the other hand, switching to the standard form served to confirm the official nature of the news reports, while switching to the dialect in explanations helped maintain communication with the recipients.
Keywords: English borrowings, Arabic media discourse, Egyptian dialect, code-mixing, foreign language insertions, YouTube news channels, code-switching